Islamic Higher Education and Legal Adaptation in Minority Communities: A Cultural Management Framework - Nento, Shinta; Abdullah, Abdul Haris (IAIN Manado, 2025)
This study aims to evaluate the role of Islamic higher education in supporting the process of Islamic law adaptation within a Muslim minority community in the city of Manado, through a cultural management approach. Manado was selected as the research locus due to its unique characteristics as a region with a Muslim minority population, which presents specific challenges in the open and adaptive implementation of Islamic law. This qualitative research approach involved in-depth interviews with stakeholders in Islamic higher education, including academics, university administrators, and local religious leaders or scholars. The findings reveal that cultural management implemented by Islamic higher education institutions in Manado plays a significant role in the contextual integration and adaptation of Islamic law, aligning with local cultural values through effective collaboration with community leaders and curriculum adjustments based on the needs of the Muslim minority. The study is expected to serve as a reference for other Islamic higher education institutions in developing responsive policies tailored to minority communities. The research also implies the need for a more inclusive model of Islamic legal adaptation, potentially contributing to the development of globally relevant Islamic legal education policies without compromising core Islamic principles.